Rates of Revision Surgery following In Situ Decompression versus Anterior Transposition for the Treatment of Idiopathic Cubital Tunnel Syndrome - Van Nest, Duncan; Ilyas, Asif M. (Journal of Hand and Microsurgery, 2019)
Objective The current understanding of revision rates following surgery for the primary surgical treatment of idiopathic cubital tunnel syndrome (CuTS) remains unclear. The purpose of this study was to describe and compare the rate of revision surgery following in situ decompression (SD) versus anterior transposition (AT) after the surgical treatment of idiopathic CuTS and examine possible predicting variables for revision.Materials and Methods A retrospective cohort study was performed at a single institution by querying records for all CuTS surgeries performed between January 2010 and December 2015. The initial query resulted in 1,967 cases. Exclusion criteria included acute trauma, concurrent unrelated primary elbow procedure, revision surgery, incomplete records, and age younger than 18 or older than 89 years. A total of 1,384 surgeries met criteria for study inclusion. A case–control study was then performed with 39 cases of revision and a group of 76 control cases that did not undergo revision surgery. Bivariate analysis followed by multivariate logistic regression was performed to evaluate predictors of revision.Results Of the 1,384 procedures, 979 were SDs (70.7%) and 405 were ATs (29.3%). Among the 1,384 total procedures, there were 39 primary cubital tunnel surgeries resulting in a revision surgery (2.8%). The revision rate for SD was 3.1% and the revision rate for AT was 2.2%. Predictors of revision were younger age, increased nerve conduction velocity, and decreased duration of symptoms.Conclusion In the surgical treatment of idiopathic CuTS, the overall revision rate is low (2.8%). This study found no significant difference in revision rate between SD and AT, but that risk for revision surgery overall was associated with younger age, increased nerve conduction velocity, and decreased duration of symptoms.Level of Evidence This is a therapeutic, level III study.